2018
DOI: 10.1016/j.compositesa.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A multi-pattern compensation method to ensure even temperature in composite materials during microwave curing process

Abstract: Microwave curing technologies have many advantages in manufacturing fiber reinforced polymer composite materials used in aerospace products, compared with traditional autoclave curing technologies. However, the uneven electromagnetic field of microwave in the cavity of the curing chamber results in uneven temperature on the surface of composite laminates during curing, which has been a major obstacle in industrial applications worldwide. Existing methods attempted to solve the problem by the random superpositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Several research activities concerning this topic were already reported. In [1] and [2] microwave applicators with magnetrons as RF (radio frequency) sources are presented. By using magnetrons, it is easily possible to change the amplitude and the pulse duration of the RF power during the heating process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research activities concerning this topic were already reported. In [1] and [2] microwave applicators with magnetrons as RF (radio frequency) sources are presented. By using magnetrons, it is easily possible to change the amplitude and the pulse duration of the RF power during the heating process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a frequency or phase tuning of magnetrons is only limited possible if not at all impossible practically. In this frame in [1] and [2], an intelligent control algorithm is used to control the amplitudes of the different magnetrons to increase the temperature uniformity of the work piece. In contrast to the magnetron, power modules that are using solid-state amplifiers (SSA) would offer the possibility to vary accurately the amplitude, frequency and phase of the RF output power.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave oven used in this experiment has an octagonal applicator with two microwave sources on each side, as shown in Fig.1 [11]. For each microwave source, the frequency is stabilized at 2.45GHz and the power range is 0~800W.…”
Section: Methodsmentioning
confidence: 99%
“…cd Q , cv Q and rd Q are the heat flux due to conduction, convection and radiation which usually can be considered as constants or even ignored compared with the absorbed microwave power, when the material properties remain constant. Thus, the HP is directly proportional to the distribution of the absorbed microvave power [11]. To investigate the influence factor of the HP, a large number of heating experiments were carried out under different conditions.…”
Section: Constant Hp-mcs Relationship In Non-transforming Materialsmentioning
confidence: 99%
“…Other research results demonstrated by Li et al [11] showed that the microwave curing technologies could reduce the cure-induced strain of composite materials. Zhou et al [12] studied the compensating method of the uneven temperature distribution of composite materials during microwave heating process. The experimental results showed improvement in temperature uniformity compared with existing microwave heating methods.…”
Section: Introductionmentioning
confidence: 99%